The Role of Karo Customary Law in the Distribution of Inherited Property among Families Without Male Descendants in Sukadame Village, Tigapanah District - Icha Florensia Br Sitepu; Maslon Hutabalian; Maria Ferba Aditya Simanjuntak (Indonesian Journal of Advanced Research, 2026)
Karo customary society adheres to a patrilineal kinship system that positions sons as both the successors of the clan name and the primary heirs. This principle raises particular problems for families without male descendants, since daughters have traditionally held an unequal position within the customary inheritance structure. This article examines how Karo customary law is applied in the distribution of inherited property in families with only daughters, and analyzes its impact on families without male descendants and those without any descendants at all, focusing on Sukadame Village, Tigapanah District. A socio-legal approach with a qualitative descriptive method was employed. Data were collected through interviews with customary leaders, community members, and the village head, supported by documentary and literature study. The analysis draws on Eugen Ehrlich’s living law theory, patrilineal kinship theory, customary inheritance law theory, and legal pluralism theory. The findings show that the Sukadame community still upholds the patrilineal system as the basis for inheritance, yet its implementation is no longer rigid, as disputes are resolved through customary deliberation (musyawarah) involving the kalimbubu, senina, and anak beru. In practice, daughters in families without sons increasingly receive equal shares of inherited property, while families without any descendants pass on their estate to close relatives such as permen and bebere through family agreement. These findings confirm that Karo customary law is adaptive: it remains a living law while adjusting to demands for gender justice and the needs of modern society.